First record of Capparimyia savastani in Greece - Papachristos, D.; Milonas, P.; Papasotirioy, M. (ENTOMOLOGIA HELLENICA, 2009)
During the summer of 2008 extensive infestation was observed on edible flower buds of wild and cultivated caper plants (Capparis sp.) in Milos island. Larvae were taken from infested plants and kept in laboratory conditions at 24±1oC, 70±5% RH, and under a photoperiod of 16:8 (L:D) h until adult’s emergence. Adults were identified as the species Capparimyia savastani (Martelli) (Diptera: Tephritidae). The presence of this species is recorded for the first time in Greece. The larvae of C. savastani fed on flower buds of caper plants and it appears to be capable to cause extensive damage on cultivated and wild caper.